Commodity prices co-movements and financial stability: A multidimensional visibility nexus with climate conditions - Flori, Andrea; Pammolli, Fabio; Spelta, Alessandro (Journal of Financial Stability, 2021)
This paper investigates the nexus between climate-related variables, commodity price co-movements and financial stability. First, we project the commodity price time series onto a multilayer network. Centrality measures computed on the network are used to detect the existence of common trends between the series and to characterize the role of different nodes during phases of market downturns and upturns, unveiling the onset of financial instability. Then, an econometric analysis is introduced to show how climate-related variables affect financial stability by influencing co-movements of commodity prices. Overall, the paper reveals how synthetic indicators of commodity price co-movements generate valuable signals to study the nexus between climate-related conditions and the dynamics of financial systems.